2017
DOI: 10.1093/nar/gkx700
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a novel antibacterial toxin that exploits elongation factor Tu to cleave specific transfer RNAs

Abstract: Contact-dependent growth inhibition (CDI) is a mechanism of inter-cellular competition in which Gram-negative bacteria exchange polymorphic toxins using type V secretion systems. Here, we present structures of the CDI toxin from Escherichia coli NC101 in ternary complex with its cognate immunity protein and elongation factor Tu (EF-Tu). The toxin binds exclusively to domain 2 of EF-Tu, partially overlapping the site that interacts with the 3′-end of aminoacyl-tRNA (aa-tRNA). The toxin exerts a unique ribonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 82 publications
1
33
0
Order By: Relevance
“…Interestingly, this CysK.CdiA-CT EC536 complex mimics the CysK.CysE complex, which is typically formed during de novo cysteine biogenesis, with a higher binding affinity (Johnson et al, 2016;Jones et al, 2017). Other examples are the recipient elongation factor Tu (EF-Tu) in activating the toxicity of CdiA-CT EC869 and CdiA-CT NC101 (Jones et al, 2017;Michalska et al, 2017), and the involvement of recipient PtsG in CdiA-CT 3006 and CdiA-CT NC101 entry (Willett et al, 2015). To summarize, a variety of the non-immunity proteins in the recipient cells affect the CDI antagonizing outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this CysK.CdiA-CT EC536 complex mimics the CysK.CysE complex, which is typically formed during de novo cysteine biogenesis, with a higher binding affinity (Johnson et al, 2016;Jones et al, 2017). Other examples are the recipient elongation factor Tu (EF-Tu) in activating the toxicity of CdiA-CT EC869 and CdiA-CT NC101 (Jones et al, 2017;Michalska et al, 2017), and the involvement of recipient PtsG in CdiA-CT 3006 and CdiA-CT NC101 entry (Willett et al, 2015). To summarize, a variety of the non-immunity proteins in the recipient cells affect the CDI antagonizing outcome.…”
Section: Introductionmentioning
confidence: 99%
“…CDI toxin‐immunity protein complexes are excellent targets for methods development in the CASP competition, because the activities of most toxins are unknown and their interactions with cognate immunity proteins are not easily predicted. Over the past several years, we have taken complementary biochemical and structural approaches to identify CDI toxin activities and explore the diversity of their interactions with immunity proteins . We recently solved the crystal structures of CdiA‐CT•CdiI complexes from E. coli 3006 (EC3006) and K. pneumoniae 342 (Kp342) at 2.20 and 2.55 å resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several years, we have taken complementary biochemical and structural approaches to identify CDI toxin activities and explore the diversity of their interactions with immunity proteins. [39][40][41][42][43] We recently solved the crystal structures of CdiA-CT•CdiI complexes from E. coli 3006 (EC3006) and…”
mentioning
confidence: 99%
“…This toxin stabilization organizes the active site for substrate recognition ( 67 ). For other CDI tRNase toxins, GTP-dependent activation by elongation factor Tu (EF-Tu) was detected ( 68 , 69 ). From the producer’s perspective, activation necessity may seem an undesirable trait, as toxin resistance may develop.…”
Section: Perspectivementioning
confidence: 99%
“…From the producer’s perspective, activation necessity may seem an undesirable trait, as toxin resistance may develop. For CDI toxins in particular, it was suggested that such activation may play a role in intercellular communication ( 55 ): toxins transferred to immune siblings could form heterotrimeric complexes (EF-Tu, CDI toxin, and immunity partner) that influence gene expression and thereby cell-to-cell signaling between clonally related cells ( 68 , 69 ). Such a toxin exchange mechanism was proposed to initiate biofilm formation in Burkholderia thailandensis ( 70 ).…”
Section: Perspectivementioning
confidence: 99%